Regulatory and methodological support of blockchain technologies - A. V. Knyazev; Yu. Yu. Cheremukhina (Омский научный вестник)
The article provides information on the state of the issue in the field of standardization of development and application of distributed ledger technology and blockchain. The current state in the development of normative documents, including documents on standardization, is analyzed. The international experience in the development of documents on standardization is reflected on the example of the International Organization for Standardization and the International Telecommunication Union, as well as the experience of developing documents in the national standardization system on the example of technical committees for standardization. Possible scenarios for the use of distributed registry technology and blockchain in the national standardization system are considered, taking into account international experience and trends in the development, development and use of national standards in digital formats, as well as promising interaction with other information technologies that are already standardized at the international and national levels.